2014
DOI: 10.1136/bjophthalmol-2014-305296
|View full text |Cite
|
Sign up to set email alerts
|

CFI-rs7356506 is a genetic protective factor for acute anterior uveitis in Chinese patients

Abstract: This study has revealed a significant association between AAU and CFI-rs7356506, suggesting that CFI is involved in the pathogenesis of AAU, and that its influence on AAU may differ depending on gender and HLA-B27 status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…As described above, CFH -rs1065489 and CFB -rs1048709 were identified as clinical markers associated with a specific disease phenotype. Moreover, joint effects between their risk genotypes conferring a strongly increased risk to uveitis were also found 1720, 23 . The molecular mechanism might be affecting the binding affinity with C3b and subsequently disturbing the activation of the alternative pathway C3-convertase (C3bBb).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…As described above, CFH -rs1065489 and CFB -rs1048709 were identified as clinical markers associated with a specific disease phenotype. Moreover, joint effects between their risk genotypes conferring a strongly increased risk to uveitis were also found 1720, 23 . The molecular mechanism might be affecting the binding affinity with C3b and subsequently disturbing the activation of the alternative pathway C3-convertase (C3bBb).…”
Section: Discussionmentioning
confidence: 87%
“…We further demonstrated that genetic variants of CFB and CFI , in the same complement alternative pathway, are risk factors for both AU and NIPU patients. Moreover, a significant joint-effect among these genes, as well as genotype and phenotype correlations was observed 17, 20, 23 . In addition, parallel studies also demonstrated that genetic variants involved in the alternative pathway, CFH and CFB , as well as C5 , considered as the “downstream” complement regulator, were also associated with type 2 diabetic retinopathy (T2DM), viewed from the perspective of inflammation 16, 22 .…”
Section: Introductionmentioning
confidence: 89%
“…Several complement genes were extensively investigated, particular attention was paid on the "upstream" functional pathways. Of them, variants in the CFH, CFB and CFI involved in the alternative pathway, were identified as genetic risk markers for various uveitis subtypes [16][17][18][19][20]. A recent report from our laboratory also demonstrated that the classical pathway gene, C1INH, as well as the central component of the cascade, C3 gene, may confer either no or limited risk for uveitis susceptibility [21,22].…”
Section: Discussionmentioning
confidence: 94%
“…Our research team have made great efforts in depicting the genetic profile of uveitis and intraocular inflammation regarding complement pathway genes, several genes have been extensively investigated and identified to be associated with many forms of uveitis, these genes included complement factor H (CFH), complement factor B (CFB), complement factor I (CFI), and CD59 [15][16][17][18][19][20]. Meanwhile, we have largely ruled out the involvement of some complement factors in the disease genetics, such as component 1 inhibitor (C1INH), and complement component 3 (C3) [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Several genetic studies have shown that polymorphisms within the complement system can affect immune‐related disease development, including how CFH, complement factor I (CFI) and complement factor B appear to be associated with anterior uveitis . CFI, which is a serine protease in the complement cascade, also appears to be associated with AAU . CFHR genes are strongly associated with different diseases involving complement dysregulation, which suggests that they play a major role in regulating complement activation through protein production .…”
Section: Introductionmentioning
confidence: 99%